2021
DOI: 10.1136/bmjopen-2021-053188
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation of patients with cholecystolithiasis in primary care: a multipractice comparative analysis

Abstract: ObjectivesTo examine general practitioners’ (GP) management of cholecystolithiasis and to evaluate persisting abdominal complaints in the years after the diagnosis.DesignRetrospective analysis of registry data and a subset of individual medical records.SettingSeventeen primary care practices affiliated with the Radboudumc Practice Based Research Network in the Netherlands.Participants633 patients with cholecystolithiasis diagnosed between 2012 and 2016.Primary and secondary outcome measuresThe primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…14 Harvard Medical School, Boston, MA, USA. 15 Division of Trauma, Emergency Surgery, and Surgical Critical Care, Massachusetts General Hospital,…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Harvard Medical School, Boston, MA, USA. 15 Division of Trauma, Emergency Surgery, and Surgical Critical Care, Massachusetts General Hospital,…”
Section: Author Contributionsmentioning
confidence: 99%
“…Still, other times, conditions may allow physicians hours or more before the treatment begins, giving patients time to learn about the potential alternatives and make an informed decision about the next medical steps. The surgical literature [13] has stressed the benefits of applying SDM in trauma and emergency surgery, including better clinical outcomes by enhancing the quality of patient's recovery [14], better managing the patient's expectations [15], and limiting surgical interventions when they are not necessary [16]. Benefits can also be gathered from the hospital's organization, as SDM provides better patient management and flow [17], stimulating patient-centric care [18] and leading to patient empowerment and co-production practices [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The authors 20 recently undertook a primary care analysis to explore general practitioner (GP) management of patients with gallstones in order to assess concomitant gastrointestinal diagnoses for pain. This study showed that 360 of 633 included patients with gallstones (57 per cent) were also diagnosed with another gastrointestinal disorder in the years before and after the diagnosis of symptomatic gallstone disease.…”
Section: Current Primary Care For Patients With Uncomplicated Cholecy...mentioning
confidence: 99%
“…Patients were most often referred to the emergency department, surgeon or gastroenterologist (47.2, 42.5, and 10.3 per cent respectively). Ultimately, 79 per cent of all referred patients underwent cholecystectomy 20 . After cholecystectomy, more than half of the patients (52 per cent) returned to the GP with persistent abdominal pain.…”
Section: Current Primary Care For Patients With Uncomplicated Cholecy...mentioning
confidence: 99%
“…In addition, the population is seriously aging [ 2 6 ]. In an increasingly obese population, cholecystolithiasis becomes a significant and growing health problem [ 7 ] and the cholecystolithiasis prevalence is rising [ 8 ]. However, cholecystolithiasis is an acute or chronic infection of the gallbladder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%